The Effect of Work Stress and Compensation on the Performance of AVSEC Unit Officers at Sultan Muhammad Salahuddin Bima Airport - Dian Rahmiyati Andayani; Arif Fakhrudin (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Human resources are the main factor needed to achieve the goals of an organization. To achieve the goals or objectives, the organization needs to improve the performance of each employee to get perfect results. One of the factors that can affect employee performance is work stress, work stress is a condition or feeling experienced by employees while working so that it makes employees feel stressed and anxious. In addition to Human Resources, Performance, and Work Stress, Compensation is also something that companies need to pay attention to, because compensation is one of the factors that can create good employee performance. This research was conducted to find out whether there is an effect of work stress and compensation on the performance of AVSEC unit officers at Sultan Muhammad Salahuddin Bima Airport. This study used quantitative research methods, and the research instrument used was a questionnaire. The results of this study indicate that: 1.) Work Stress partially affects the Performance of Avsec Unit Officers at Sultan Muhammad Salahuddin Bima Airport, 2.) Partially Compensation does not affect the Performance of Avsec Unit Officers at Sultan Muhammad Salahuddin Bima Airport. 3.) Work Stress and Compensation simultaneously affect the performance of Avsec Unit Officers at Sultan Muhammad Salahuddin Bima Airport.